Regular enumerations for abstract structures (Annual of Sofia University St. Kliment Ohridski. Faculty of Mathematics and Informatics, 2001)
Using the method of regular enumerations in the context of definability, we obtain a normal form for the sets which are $\sum_{n+1}$-admissible in some partial structure.